Painting in Tempera, c. 1900 - Gómez González, Marisa (Ge-conservacion, 2018)
Painting in Tempera, c. 1900 Karoline Beltinger (SIK-ISEA), Zurich & Jillen Nadolny (Art Analysis & Research) London eds. Publicado por Schweizerisches Institut für Kunstwissenschaft (SIK-ISEA) y Archetype Publications Ltd 2016 ISBN: 9781909492448 Dimensiones: 297 x 210 Páginas: 264 Ilustraciones en color